1959
DOI: 10.1002/jsfa.2740100606
|View full text |Cite
|
Sign up to set email alerts
|

Souring of South African tomato juice by Bacillus coagulans

Abstract: The occurrence of flat‐sour spoilage in South African tomato juice is reported and the biochemical characteristics, D and z values, of the causative organism are described. pH adjustment to prevent spore germination, as originally proposed by Pederson & Becker, is suggested as the simplest control measure. The inhibition of B. coagulans by tomato juice when added to culture media is apparently a pH effect. The failure of B. coagulans to produce gas in canned tomato juice is due to a restricted oxygen supply, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1963
1963
1994
1994

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…At p H 4.4 and a t p H 6.3 the thermal resistance was higher in the cations containing tomato juice solution than in the evaporated milk solution. Anderson, Esselen & Fellers (1949) and Knock, Lambrechts, Hunter & Riley (1959) demonstrated that the phosphate concentration in the heating medium, the p H and several other factors affect the heat resistance of the spores. Frank & Campbell (1957) showed that the rate of thermal destruction of the spores of B. coagulans can be nonlogarithmic:…”
mentioning
confidence: 99%
“…At p H 4.4 and a t p H 6.3 the thermal resistance was higher in the cations containing tomato juice solution than in the evaporated milk solution. Anderson, Esselen & Fellers (1949) and Knock, Lambrechts, Hunter & Riley (1959) demonstrated that the phosphate concentration in the heating medium, the p H and several other factors affect the heat resistance of the spores. Frank & Campbell (1957) showed that the rate of thermal destruction of the spores of B. coagulans can be nonlogarithmic:…”
mentioning
confidence: 99%